The predictive value of the interferon-γ release assay for chemotherapy responses in patients with advanced non-small-cell lung cancer. (January 2018) - Huang, Hsu-Ching; Su, Wei-Juin; Chiang, Chi-Lu; Feng, Jia-Yih; Huang, Hsin-Yi; Lin, Ching-Hsiung; Lin, Sheng-Hao; Cheng, Ching-Yuan; Chiu, Chao-Hua
Highlights: Phytohemagglutinin-stimulated IFN-γ (PSIG) level may represent one's immune status. Patients with lower pre-chemotherapy PSIG levels had shorter survival time. Patients with lower pre-chemotherapy PSIG levels had lower disease control rate. An adequate immune function may be a prerequisite for chemotherapy response. Abstract: Objectives: IFN-γ takes part in immunologic responses to cancer and its interactions with chemotherapy have also been described. Our previous study had showed an association between phytohemagglutinin (PHA)-stimulated IFN-γ (PSIG) response and overall survival in patients with advanced non-small-cell lung cancer (NSCLC). Here, we aimed to evaluate the correlation between PSIG and chemotherapy responses. Materials and methods: From January 2011 to August 2012, 340 newly diagnosed patients with lung cancer were enrolled in a prospective latent tuberculosis observational study. Patients with advanced NSCLC who were treated with chemotherapy were included in this analysis. An IFN-γ release assay (IGRA) was used to evaluate pre-treatment PSIG levels. Patients were grouped into low and high PHA response groups according to their PSIG levels. Their demographic characteristics, tumor responses, and survival rates were investigated. Results: Eighty-four patients were enrolled. The chemotherapy response rates in the high and low PHA response groups were 45.2% and 35.7% ( p  = 0.190), respectively. The disease control rate in the high PHA response group was 76.2%, versus 52.4% in the low PHA response group ( p  = 0. 023). In multivariate analysis, PHA response was an independent predictor of disease control (odds ratio = 3.017, 95% confidence interval = 1.115–8.165). The Kaplan-Meier method demonstrated both longer progression-free survival ( p  = 0.008) and overall survival ( p  = 0.003) in the high PHA response group. Conclusions: A higher pre-treatment PSIG response, obtained using the IGRA, was associated with better disease control rate and survival among patients with advanced NSCLC treated with chemotherapy.